Life in Wales - Dodd, A. H. (Arthur Herbert) (London : Batsford, 1972)
Describes Welsh life and customs, from the time of the earliest workers of flint tools and weapons down to the emergence of political nationalism in the nineteenth and twentieth centuries.
Includes bibliographical references.
1
Keywords: Wales -- History -- Juvenile literature; Wales -- Social life and customs -- Juvenile literature